(untitled) (Strathmore Law Journal, 2021)
Described as the common heritage of humanity by Arvid Pardo in 1967, the sea has always been unanimously recognised as a source of life. Hosting most of the world’s living and non-living resources, the sea has always attracted human’s attention. From organised expeditions in search of new land to fishing, the sea has contributed to the economic, social and cultural development of many nations. Despite extensive developments made in the road and air transportation systems to facilitate trade, the sea still plays an active part in international trade. According to the United Nations Conference on Trade and Development (UNCTAD), 80% of goods traded worldwide are carried by sea and as per the UNCTAD Review of Maritime Transport 2020, the volume of seaborne trade for 2019 reached 11.08 billion tons. Currently, many countries and regional blocs are converging towards this concept of maritime security in order to restore peace and stability at sea. In Africa, for instance, maritime security is expressly defined in Africa’s Integrated Maritime Strategy 2050 (2050 AIM Strategy). This article is devoted to examine the status questionis of the treaties and legislation application.